Die Bedeutung des Wettbewerbsrechts im Vergaberecht - Park, Jongwook (Beiträge zum Vergaberecht, 2021)
»The Significance of Competition Law in Public Procurement Law«: The study deals with the significance of competition law in public procurement law. In this study, it is underlined that the practical significance of competition law in public procurement law is low, because public procurement law already has Instruments of its own that can prevent different competition problems without the detour via the competition law.